Three vectors are expressed in terms of other three vectors in the form of a=a1α + a2β + a3γ b=b1α + b2β + b3γ c=c1α + c2β + c3γ How to show that a.(bxc) = λ α.(βxγ) and find out λ? I knew the first part where we carry out dot and product rule for vectors a.(bxc), but the other side of the equation I have no idea how to start with. Anyone knows how to do this? Thanks.
a=a1(alpha) + a2(beta) + a3(gamma) b=b1(alpha) + b2(beta) + b3(gamma) c=c1(alpha) + c2(beta) + c3(gamma) How to show that a.(bxc) = λ (alpha) .(beta x gamma) and find out λ?